Saint Vincent and the Grenadines. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Saint Vincent and the Grenadines during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as resilience against climate change, biosecurity, export, trade, good agricultural practices, health and food safety. Finally, support was given to improving plant tissue culture and the coffee and coconut value chains.